A INFLUÊNCIA DE TIPOS DE GUARDA-CORPOS NA VENTILAÇÃO DE EDIFÍCIOS MULTIFAMILIARES VERTICAIS - Raviolo, Bruno; Leite, Renan Cid; Fontenelle, Thais (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
Stating the natural ventilation relevance to thermal comfort in hot and humid climate regions, this paper investigates potential solutions to identified problems in multistory residential building typology. Through an inductive scientific method, different types of railings used in balconies are evaluated for their influence on the intensity and pattern distribution of the pressure coefficient on buildings' frontal facades. Research methods includes a survey carried with a group of architects from Fortaleza to clarify design criteria when choosing railings; documental research to build a study case with typological value; computational fluid dynamics simulations to assess railings performance. Results compares the intensity and pattern distribution of the pressure coefficient modified by balconies and its railings between different stories. Discussions includes general design guidelines to adequate technical drawings detailing guard railings during architectural design, thus minimizing natural ventilation issues identified in this typology.